Careers guidance in context - Gothard, W. P. (SAGE, 2001)
Helping others to make occupational choices requires a combination of skill and a deep understanding of the world of work as it is today and as it will be in the future. Unlike texts which focus only on skill, Careers Guidance in Context is designed to develop understanding of the social, economic and political factors which shape both the labour market and careers guidance as an occupation in itself.